Demarcation of Criminal Liability of Notary Publics in the Falsification of Authentic Deeds: Examination of Supreme Court Decision Number 933 K/Pid/2023 - Detiandri, Laras; Riyanto, Astim; Setiawan, I Ketut Oka (CV. Social Politic Genius (SIGn), 2026)
Notaries public as public officials hold the attributive authority to issue authentic deeds, but this instrument is vulnerable to manipulation due to the disregard of the principle of prudence. A crucial problem arises due to the absence of uniform dogmatic parameters in distinguishing professional administrative negligence from the criminal intent of notaries public in the criminal act of falsification. This has implications for massive civil losses for third parties and triggers a disparity in judicial decisions. This research aims to evaluate the distinction between administrative negligence and conditional intent and to reconstruct the application of the doctrine of participation to public officials by examining the legal considerations in Supreme Court Decision Number 933 K/Pid/2023. Utilizing a normative legal research method through the statute, case, and conceptual approaches, legal materials are analyzed using a juridical qualitative method with deductive syllogism reasoning. The examination results prove that the active action of a notary public ignoring a clear written warning regarding defective documents and inserting them into the minutiae of the deed converts negligence into conditional intent that legally fulfills the elements of Article 264 section (1) of the Penal Code. This action fulfills the requirement of joint physical implementation in the crime of falsifying an authentic letter. Such action degrades the perfect evidentiary value of the deed into an underhanded act, resulting in civil losses amounting to billions of rupiahs. The cassation decision absolutely establishes the Defendant’s criminal liability, simultaneously voiding the legal protection right of the Notary Honorary Council. This research concludes that the notarial mandate does not provide immunity against structural crimes. Therefore, it is recommended that the Ministry of Law of the Republic of Indonesia reform the supervision regulation to revoke professional protection at the initial investigation stage if an active action is proven, and to establish this decision as established jurisprudence to restore the legal certainty of evidentiary instruments in Indonesia.